Comparison of bending fracture strength of silicon after ablation with nanosecond and picosecond lasers. Issue 9 (June 2016) - Noh, Jiwhan; Kim, Jae-Hyun; Sohn, Hyonkee; Lee, Jae-Hoon
Abstract The demands of drilling on silicon wafers in multi-chip packages (MCPs) that employ laser ablation have increased. In this study, the bending fracture strengths of silicon specimens were experimentally measured using a four-point bending test after ablation with nanosecond and picosecond lasers. The specimens drilled with the picosecond laser showed a mean bending fracture strength (1530 MPa) higher than that of the specimens drilled with the nanosecond laser (678 MPa). One reason for this difference is that the cross-sectional roughnesses of the specimens drilled with the picosecond laser were less than those of the samples drilled with the nanosecond laser. Consequently, for the purpose of MCP interconnections, silicon wafer drilling with a picosecond laser is preferable to drilling with a nanosecond laser since the former yields greater bending fracture strength.